(untitled) (Shahroud Journal of Medical Sciences, 2019)
Background: Mother's health and breastfeeding efficacy are affected by depression during pregnancy. The aim of study was to determine the effects of cognitive-behavioral therapy on the treatment of postpartum depression in mothers after childbirth. Methods: In this systematic review, the Web of Sciences, PubMed, Scopus, Google Scholar, Iran Medex, Magiran & SID databases were used to access relevant documentation. To search for articles in the resource, the keywords depression AND cognitive-behavior therapy AND "perinatal OR antepartum OR childbirth" is used with all possible combinations of these words. Without time limitation, all related articles have been retrieved. Search was restricted to articles published in Persian and English. The quality of papers was examined using the Cochran risk of bias tool. Meta-analysis was performed using Rev 5.3. Results: We retrieved 621 titles, of which 12 were qualified after the qualitative synthesis. Meta-analysis revealed a statistically significant beneficial effect of CBT sessions as compared to routine postpartum care on long term management of postpartum depression. (Mean Difference: -4.02 [-5.58, -2.47]). A pooled effect size with BID instrument was observed -6.32 [-8.54, -4.11] at 3 months, with EPDS were observed -2.83 [-6.56, 0.90] and -2.81 [-4.21, -1.41] at 3 and 6 months respectively. Conclusions: CBT was shown to be effective however the evidence available is limited. It can be used as an effective psychological treatment without the side effect of drugs in PPD. Keywords: Postpartum depression, Cognitive behavioral therapy, Psychological disorder, Review, Meta-analysis.